Development of Problem Based Learning E-module Based on Research Hormone Leptin Levels in Rats Hyperglycemic - Atika Anggraini; Sri Rahayu Lestari*; Murni Saptasari (Universitas Syiah Kuala, 2022)
One cause of low student understanding of the material is the hormone leptin, a less comprehensive learning resource. Problem Based Learning is one of the demands in education that must be taught to students, one of the ways to use the results of research on the levels of the hormone leptin in rats hyperglycemic as a learning resource. This study aims to develop a problem-based learning-based e-module based on research hormone leptin levels in rats hyperglycemic invalid and practical. The e-module is developed based on the stages of the ADDIE development model. The e-module has developed later through the validation stage of the material and media experts. The practicality test was carried out by educational practitioners and 15 students who had taken the Endocrinology course at the State University of Malang. The data analysis technique used quantitative data in the form of a validation scores of material experts, media experts, and practicality. The data collected in the form of qualitative data in the form of comments and suggestions validators. The results obtained from the results of the validation of material experts were 91.66%, teaching materials experts 92.11%, field trials expert practitioners 95.83%, and the average student response 86.54%. Based on these results, e-module can be very valid and practical for use in teaching and learning